(3GdLeY Hjf GdCNHGQ GdeJYGQVIs - (3GdHgHgGfj, eMeO GdHgHgGfj, eMeO HGbQ Hf eMeO Cced GdCUagGfj, J (B1205(3g` (B1891(3es ((3GdeTgO GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3hHYO, gPg QSGdI aj GdLeY Hjf GdCNHGQ (B... (3bhdg ajMed Ydi GdGSJMHGH eQGOg HGdMed Ydi GdGSJMHGH HfGA Ydi GdebOeI GdeTghQI YfOge ef Cf GdLeY Chdi ef GdWQMs
(3BNQgG (B:s
(3BNQgG(B: (3fYe Zf MUd ef GdbQjfI GdXf HGdeQGO agh CeQ CNQ aJCed gPg GdCbSGe ef GdLeY eG SfM HNGWQj GdaGJQ hCeG ZjQgG ef CbSGe GdLeY adh cGf eJMbbG jYde MGdg eeG PcQs
(3HBNQgG aGFOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf L (B3: 154s
(3GdPQjYI, L (B5: 96s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3CUhd Gdabgs